THE VULNERABILITY OF THE CHURCH – ECCLESIOLOGICAL OBSERVATIONS - Punt, Leo J. (2009)
The Decade to Overcome Violence requires a spirituality that acknowledges one’s own vulnerability. What does this mean for ecclesiology? The author suggests distinguishing four aspects, i.e. physical, moral, communicative and compassionate vulnerability. In order to prevent an abstract, if not docetic type of ecclesiology, the key issue is how to deal with the moral vulnerability of the church. Several traditional strategies are no longer really satisfactory. A preferable way to keep ecclesiology connected with real church life is by taking liturgy as the point of departure. Furthermore, the author suggests to distinguish four ‘quality markers’ of the church, to be used to link the theological proprietates of the church of faith with the practical aspects of church life: inclusivity, authenticity, conciliarity and integrity. Different aspects of vulnerability can be connected with these quality markers.
Keywords: Church Law; Ecclesiology; Liturgy; Sin; Vulnerability